2013
DOI: 10.1002/phar.1260
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular Aripiprazole in the Acute Management of Psychomotor Agitation

Abstract: Aripiprazole was effective and safe in reducing acute agitation in patients with bipolar disorder or schizophrenia. Our results compare favorably to double-blind trials, probably due to higher expectations in trials involving no placebo arm. Absence of side effects could be related to the short observation time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 56 publications
1
14
0
4
Order By: Relevance
“…In some published observational studies the levels of agitation are similar to those presented here (23)(24)(25)(26)(27). These studies have demonstrated various degrees of effect of intramuscular psychotropics.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…In some published observational studies the levels of agitation are similar to those presented here (23)(24)(25)(26)(27). These studies have demonstrated various degrees of effect of intramuscular psychotropics.…”
Section: Resultssupporting
confidence: 80%
“…In several previous observational studies post-injection assessment has been recorded with frequent intervals, usually after 15, 30, 60, 90, and 120 min (23,25,26). We were not able to obtain such frequent recordings, but aimed to achieve PANSS-EC at least once within the first 2 h following injection.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…After the first month, the patient is discharged and AOM is administered monthly thereafter. In fact, we found repeated administration of 9.75 aripiprazole IM to be effective in treating acute psychomotor agitation in acutely psychotic patients (83); this formulation has shown anti-aggressive effects in psychosis-elicited aggression, although the quality of evidence of the studies considered in this systematic review was quite poor (84).…”
Section: Other Issuesmentioning
confidence: 90%
“…Because of the strength of evidence for efficacy in alleviating agitation in this population, aripiprazole IM (level 2),125, 126 lorazepam IM (level 2),125, 127 loxapine inhaled (Level 1)128, 129 and olanzapine IM (level 2)127, 130, 131, 132, 133 are recommended as the first‐line option. Sublingual asenapine (level 3),134 haloperidol IM (level 3),131, 135, 136 haloperidol IM + midazolam IM (level 3),131, 137 haloperidol IM + promethazine IM (level 3),131, 137, 138 risperidone ODT (level 3),136 and ziprasidone IM (level 3)131, 137, 139 are recommended as a second‐line treatment.…”
Section: Acute Management Of Bipolar Maniamentioning
confidence: 99%